PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRADING PLACES TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 16 PADANG - Febriani, Dewi; Zulfaneti, Zulfaneti; Melisa, Melisa (Pendidikan Matematika, 2013)
The background of this research is that the studentsâ mathematical concept apprehensions are low, that can be seen from the points of 2nd-final-semester examination of VIII-grade students of SMPN 16 Padang of the year 2012/2013. The purposes of this research is to know whether the studentsâ mathematical concept apprehensions by applying the trading-places-type active learning strategy is better than that using the conventional learning for the IX-grade students of SMPN 16 Padang. This is experimental research with Random to Subject design. The population in this research is the IX-grade students of SMPN 16 Padang of the year 2013/2014, consisting of six classes from IX2 to IX7 classes, except for IX1 class that is excellent students. The technique of sampling is total sampling. The sample classes were determined randomly so that the IX4 was selected as an experimental class and the IX6 as a control. The instrument used in this research is test for the mathematical concept apprehension in the form of essay with the test reliability of r11 = 0.89. The technique of data analysis applied is t test of one party with assistance of software MINITAB. Based on the results of data analysis, it is known that both sample classes distribute normally and homogenously on the level of Î± = 0.05 and the hypothesis tes is P value = 0.021, meaning smaller than Î± = 0.05. So that the hypothesis is accepted, that means that the studentsâ mathematical concept apprehension using the trading-places-type active learning strategy is better than that using the conventional learning for the IX-grade students of SMPN 16 Padang with the trust level of 95%..